Local Probes of Graphene Lattice Dynamics. Issue 5 (8th March 2020) - Kröger, Jörg; Néel, Nicolas; Wehling, Tim Oliver; Brandbyge, Mads
Abstract: Inelastic electron tunneling spectroscopy with a scanning tunneling microscope is a powerful method to excite and detect vibrational quanta with atomic resolution. The focus of this review article is on the local spectroscopy of graphene phonons. The experimental observation of their spectroscopic signatures together with theoretical modeling highlight the importance of the graphene–surface as well as the graphene–tip hybridization, the electron–phonon coupling strength, phonon‐mediated tunneling, local doping profiles, and the phonon density of state for the measured signal. Meanwhile, a comprehensive understanding of the underlying mechanisms has been attained and justifies an overview on available findings. Abstract : Inelastic electron tunneling spectroscopy of graphene phonons on various substrate surfaces is performed with a low‐temperature scanning tunneling microscope. The spectroscopic signal strength varies depending on the graphene–substrate combination. A theoretical picture considering phonon‐mediated tunneling, band mixing, the graphene–electrode hybridization, and the electron–phonon coupling captures the basic physics.